Hadean crustal evolution revisited: New constraints from Pb-Hf isotope systematics of the Jack Hills zircons - Kemp, A.; Wilde, Simon; Hawkesworth, C.; Coath, C.; Nemchin, Alexander; Pidgeon, Robert; Vervoort, J.; DuFrane, S. (Elsevier Science BV, 2010)
Detrital zircon crystals from the Jack Hills metasedimentary belt, Western Australia, are the only surviving vestiges of Hadean crust and represent an extraordinary archive into the nature of the early Earth. We report the results of an in situ isotopic study of 68 Jack Hills zircons in which the Hf and Pb isotope ratios were measured concurrently, allowing a better integration of isotope tracer information (176Hf/177Hf) with crystallization age (207Pb/206Pb). These data are augmented by Hf isotope data from zircons of the surrounding Narryer gneisses (3.65–3.30 Ga) and from Neoarchaean granites that intrude the Jack Hills belt. The detrital zircons define a subchondritic εHf–time array that attests to a far simpler evolution for the Hadean Earth than claimed by recent studies.This evolution is consistent with the protracted intra-crustal reworking of an enriched, dominantly mafic protolith that was extracted from primordial mantle at 4.4–4.5 Ga, perhaps during the solidification of a terrestrial magma ocean. There is no evidence for the existence of strongly depleted Hadean mantle, or for juvenile input into the parental magmas to the Jack Hills zircons. This simple Hf isotope evolution is difficult to reconcile with modern plate tectonic processes. Strongly unradiogenic Hf isotope compositions of zircons from several Archaean gneiss terranes, including the Narryer and Acasta gneisses, suggest that Hadean source reservoirs were tapped by granitic magmas throughout the Archaean. This supports the notion of a long-lived and globally extensive Hadean protocrust that may have comprised the nuclei of some Archaean cratons.